2015
DOI: 10.1016/j.fertnstert.2015.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Presence of human papillomavirus in semen of healthy men is firmly associated with HPV infections of the penile epithelium

Abstract: HPV-DNA presence in semen of healthy men is common and associated with HPV infections of the penile epithelium. HPV-DNA presence in semen may result from desquamation of HPV-infected penile cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
(46 reference statements)
2
21
2
Order By: Relevance
“…Human papillomavirus DNA in semen might originate from a male genital tract reservoir or could be a result of contamination of HPV from the skin/mucosa during ejaculation. In agreement with the results of Golob et al () and Luttmer et al (), the control group in this study showed a high prevalence of HPV DNA on genital skin swabs and in semen, and the concordance of HPV genotypes detected in the two locations was high.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Human papillomavirus DNA in semen might originate from a male genital tract reservoir or could be a result of contamination of HPV from the skin/mucosa during ejaculation. In agreement with the results of Golob et al () and Luttmer et al (), the control group in this study showed a high prevalence of HPV DNA on genital skin swabs and in semen, and the concordance of HPV genotypes detected in the two locations was high.…”
Section: Discussionsupporting
confidence: 93%
“…In a Danish study, we detected HPV in the spermatozoa from 16% of human sperm donors, and in 2/3 (10.6%), high‐risk types of HPV were detected (Kaspersen et al, ). Studies have suggested that seminal HPV originates from urogenital tract reservoirs (Damke et al, ) or from genital skin or mucosa (Giovannelli et al, ; Golob et al, ; Luttmer et al, ). Possible seminal “HPV contamination” from the genital skin and mucosa is supported by near associations between HPV types detected in the semen and on genital skin (Golob et al, ; Luttmer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Luttmer et al studying Human Papilloma virus (HPV) have found a high prevalence of this virus in semen – 27.2% of healthy adults in Amsterdam – and using fluorescence in situ hybridization (FISH) for HPV-DNA and immunocytochemistry for the HPV-L1 and HPV-E4 proteins, the authors detected HPV-DNA, HPV-E4 and HPV-L1 in exfoliated keratinocytes present in some HPV16-positive semen samples, indicating the presence of HPV viral particles [28].…”
Section: Discussionmentioning
confidence: 99%
“…Covariates were derived from a risk factor questionnaire that was administered at each visit, which was described and validated previously [34,86,69,91,23,1]. Questions covered sociodemographic characteristics, sexual behaviors, sex partnerships, and condom use.…”
Section: Details Of the Hpv In Men Data And Selection Of Covariate Vamentioning
confidence: 99%
“…Covariates were selected for inclusion in the model based on known risk factors identified in the literature for HPV in men [34,33,35,37,83,84,85,94,44,91,23,69,1]. We also included country of residence as a covariate.…”
Section: Details Of the Hpv In Men Data And Selection Of Covariate Vamentioning
confidence: 99%